2021
DOI: 10.1039/d0se01664k
|View full text |Cite
|
Sign up to set email alerts
|

Bio-oil and biochar production from halophyte biomass: effects of pre-treatment and temperature on Salicornia bigelovii pyrolysis

Abstract: Salicornia bigelovii (SB), a strategically important plant in many regions to its ability to grow in arid climates and saline water. This study evaluates the effects of halophyte biomass pre-treatment...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 49 publications
5
43
0
Order By: Relevance
“…Meanwhile, the decrease in bio-oil yield as the pyrolysis temperature increased further to 600 °C was due to the further cracking of the products at a temperature above 500 °C, generating non-condensable gases, such as CH 4 , CO, and CO 2 , as reported in the previous study. 34,35 This was supported by the fact that the gas yield significantly increased with increasing the temperature from 400 °C to 600 °C. The enhancement of the gas yield might also be due to the high presence of alkali and alkaline earth metal species in the Sargassum sp.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Meanwhile, the decrease in bio-oil yield as the pyrolysis temperature increased further to 600 °C was due to the further cracking of the products at a temperature above 500 °C, generating non-condensable gases, such as CH 4 , CO, and CO 2 , as reported in the previous study. 34,35 This was supported by the fact that the gas yield significantly increased with increasing the temperature from 400 °C to 600 °C. The enhancement of the gas yield might also be due to the high presence of alkali and alkaline earth metal species in the Sargassum sp.…”
Section: Resultsmentioning
confidence: 90%
“…46 The main component of N -aromatic compounds observed in this study was heterocyclic derivatives, such as pyrazine, pyridine, 3-hydroxy pyridine, 2-imidazolidinone, and 4-aminopyridine. The finding of this study follows the previous research by Iaccarino et al , 34 who reported that amino acids could undergo decarboxylation, cyclization, and dehydration to generate the N-heterocyclic derivatives during the pyrolysis of Salicornia bigelovii .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations